In absolute or relative terms? How framing prices affects the consumer price sensitivity of health plan choice - Hendrik Schmitz; Nicolas R. Ziebarth (Institute for the Study of Labor (IZA), 2011)
This paper provides field evidence on (a) how price framing affects consumers' decision to switch health insurance plans and (b) how the price elasticity of demand for health insurance can be influenced by policymakers through simple regulatory efforts. In 2009, in order to foster competition among health insurance companies, German federal regulation required health insurance companies to express price differences between health plans in absolute Euro values rather than percentage point payroll tax differences. Using individual-level panel data, as well as aggregated health plan-level panel data, we find that the reform led to a sixfold increase in an individual's switching probability and a threefold demand elasticity increase.
urn:nbn:de:101:1-201202285103
Keywords: H51; I11; I18; 330; health insurance; health plan switching; price competition; price elasticity; SOEP; Gesetzliche Krankenversicherung; Preiselastizität; Konsumentenverhalten; Framing; Preiswettbewerb; Gesundheitsreform; Deutschland